Syntheses and Antibacterial Studies of Some 1-Phenyl-3-(4-(2-ethanoloxy) phenyl)-5-aryl-1H-pyrazoles. (20th June 2012) - Goyal, Anju; Jain, Sandeep
Abstract : A series of 1-phenyl-3-(4-(2-ethanoloxy) phenyl)-5-aryl-1 H -pyrazoles were synthesized from chalcones, that is, 3-aryl-1-(4-hydroxyphenyl) prop-2-en-1-ones and studied for their in vitro antibacterial activity. Chalcones 1 on reaction with phenyl hydrazine in the presence of acetic acid and few drops of hydrochloric acid yielded the corresponding 1-phenyl-3-(4-hydroxyphenyl)-5-aryl-1 H -pyrazoles 2 which on further reaction with 2-chloroethanol furnished the title compounds 3 . These compounds were characterized by CHN analyses, IR, mass and 1 H NMR spectral data. All the compounds were evaluated for their in vitro antibacterial activity against two Gram positive strains ( Bacillus subtilis and Staphylococcus aureus ) and two Gram negative strains ( Escherichia coli and Pseudomonas aeruginosa ), and their minimum inhibitory concentration (MIC) was determined.